Abstraction of phenol onto Pseudomonas putida and Cetyl Trimethyl Ammonium Bromide - Saravani, N.; Arulmozhi, M.; Anbuthangam, A.; Manimozhi, M. (Cellular and Molecular Biology, 2017)
Foam separation, an efficient downstream processing unit operation, was tested as a post-treatment technique for phenol removal after biosorption. The biosorptive foam separation process was carried out in two stages, namely biosorption and foam separation. A minimum run resolution V central composite design with four variables (initial concentration, pH, biosorbent dosage, and time) for biosorption and three variables (liquid pool height, surfactant concentration, and air flow rate) for biosorptive foam separation was applied to optimize the process. The results showed a good fit with the proposed statistical model for removal of phenol (R2 = 0.9500) for biosorption and (R2 =0.9599) for biosorptive foam separation. In addition, the adsorption isotherm and kinetic studies revealed that the biosorption process followed the Langmuir model (R2=0.9544) and Bangham kinetic model (R2=0.9857). The adsorbed chemical species was identified by FTIR spectroscopy. Electrokinetic measurements were carried out to determine the isoelectric point (IEP) of the bacteria. The zeta potential profile of the bacteria appears to be negative throughout the range of pH examined, showing isoelectric point at a pH of 3. The recovery of phenol loaded biomass and final traces of phenol by flotation were found to be 99.95%.